Entanglement Classification – A Comparative Study Of Su(2) And Sl(2) Developed Operator Model - Amirul Asyraf Zhahir; Siti Munirah Mohd; Mohd Ilias M.Shuhud; Bahari Idrus; Hishamuddin Zainuddin; Nurhidaya Mohamad Jan; Mohamed Ridza Wahiddin (Institute of Advanced Engineering and Science (IAES) in collaboration with Intelektual Pustaka Media Utama (IPMU)., 2024)
Non-Indexed Publication